Kepuasan Pasien, Mutu Pelayanan, dan Fasilitas Puskesmas dalam Membangun Loyalitas Pasien di Puskesmas Kuala Behe - Tapianus Topo; Sumeidi Kadarisman; Rulia Rulia; Rahadian Malik; Kosasih Kosasih (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the impact of patient satisfaction, service quality, and health facility availability on outpatient loyalty at Kuala Behe Public Health Center, West Kalimantan. The background of this research is based on the importance of understanding factors that influence patient loyalty, as loyalty is a key indicator of the sustainability of healthcare services at the primary care level. The research employed a quantitative approach with 139 outpatient respondents selected through purposive sampling. Data were collected using a structured questionnaire designed based on indicators of patient satisfaction, service quality, health facilities, and patient loyalty. The data were analyzed using multiple linear regression with SPSS version 26. The average scores on a 5-point scale indicate that most patients rated the healthcare services as good. The t-test results show that patient satisfaction (KPRJ) does not have a significant effect on outpatient loyalty (t = 0.223; sig. 0.824 > 0.05). In contrast, service quality (MP) has a significant and positive effect on patient loyalty (t = 4.157; sig. 0.000 < 0.05). Likewise, health facilities (FP) significantly affect patient loyalty (t = 4.812; sig. 0.000 < 0.05). These findings suggest that outpatient loyalty is more strongly influenced by service quality and facility availability than by patient satisfaction alone.